DEVELOPMENT OF RESEARCHERSINFORMATION AND COMMUNICATION COMPETENCE WITH THE USE OF EPRINTS (PEDAGOGICAL EXPERIMENT) (Journal of Information Technologies in Education (ITE), 2015)
The paper is provided analysis of result of the implementation methods using EPrints system as a means of information and communication support research activities for the development of  information and communication competence of scientific and pedagogical staff. Actuality of the problem is explained intensification of scientific activity, that can be carried out thanks to the presence necessary information and communication support and information and communication competency researchers. The purpose of research is to analyze the results of the implementation the author's methodology such as tools of information and communication support to research activities in the field of pedagogical sciences EPrints using the system for the development of information and communication competency researchers.     There are proposed a three level for evaluation of researchers information and communication competence: basic level, professionally-functional level and professionallyeffective level. While choosing criteria for formation of expertise researchers in the field of pedagogical sciences information and communication competence is taken into account the content of components of the structure of information and communication competence: cognitive;operational and activity; values and motivation; creative. There are identified the perspectives of research that is to further develop methods of using open electronic systems as a means of information and communication support of scientific activities for the development of researchers information and communication competence.
Keywords: information and communication support research activities; information and communication technologies; system EPrints